Isolation of Campylobacter spp. from three species of antarctic penguins in different geographic locations - García Peña, F.J.; Llorente, M.T.; Serrano, T.; Ruano, M.J.; Belliure, J.; Benzal, J.; Herrera León, S.; Vidal, V.; D'amico, Veronica Laura; Pérez Boto, D.; Barbosa, A. (EcoHealth)
The presence of Campylobacter species was studied in three Antarctic penguin species, Adélie (Pygoscelis adeliae), chinstrap (Pygoscelis antarctica) and gentoo (Pygoscelis papua). A total of 390 penguins were captured in 12 different rookeries along the Antarctic Peninsula with differences in the amount of human visitation: six colonies were highly visited [Stranger Point, King George Island (P. papua and P. adeliae); Hannah Point, Livingston Island (P. papua and P. antarctica); Deception Island (P. antarctica); and Paradise Bay, Antarctic Peninsula (P. papua)], and six colonies were rarely visited [Devil’s Point, Byers Peninsula, Livingston Island (P. papua); Cierva Cove, Antarctic Peninsula (P. papua); Rongé Island (P. papua and P. antarctica); Yalour Island (P. adeliae); and Avian Island (P. adeliae)]. A total of 23 strains were isolated from penguins from nine different rookeries. Campylobacter lari subsp. lari was isolated from eight samples (seven from P. papua and one from P. adeliae); C. lari subsp. concheus from 13 (ten from P. adeliae and three from P. antarctica) and C. volucris from two samples (both from P. papua). We did not find any significant differences in the prevalence of Campylobacter spp. between the populations in highly and rarely visited areas. This is the first report of C. lari subsp. concheus and C. volucris isolation from penguins in the Antarctic region. Fil: García Peña, F.J. Laboratorio Central de Veterinaria de Algete; España Fil: Llorente, M.T. Centro Nacional de Microbiología, Instituto de Salud Carlos III; España Fil: Serrano, T. Grupo TRAGSA; España Fil: Ruano, M.J. Laboratorio Central de Veterinaria de Algete; España Fil: Belliure, J. Universidad de Alcalá; España Fil: Benzal, J. Consejo Superior de Investigaciones Científicas. Estación Experimental de Zonas Aridas; España Fil: Herrera León, S. Centro Nacional de MicrobiologíaInstituto de Salud Carlos III; España Fil: Vidal, V. Consejo Superior de Investigaciones Cientificas. Museo Nacional de Ciencias ...